(1227) Conditions and methods of investment projects evaluation in the economy of developing countries شروط وأساليب تقييم المشاريع الاستثمارية في اقتصاد البلدان النامية - Muller, Alexander (The Institute Of National Planning., 2018)
The problem of new investment projects evaluation in developing countries is one of the most difficult economic problems in the sphere of theory and practice of development of those countries.